Efficient removal of crystal violet and acid red 88 dyes from aqueous environments using easily synthesized copper ferrite nanoparticles - Asma S. Al-Wasidi; Ehab A. Abdelrahman; Khalil ur Rehman; Fawaz A. Saad; Alaa M. Munshi (Scientific Reports)
Abstract This study details the synthesis and application of magnetic copper ferrite (CuFe2O4) nanoparticles for the efficient removal of acid red 88 and crystal violet dyes from aqueous solutions. Utilizing a combustion method, nanoparticles were synthesized with succinic and malic acids as fuels, yielding samples with crystallite sizes of 28.54 ± 0.90 nm for the sample synthesized with malic acid and 19.79 ± 0.75 nm for the sample synthesized with succinic acid. Optimum removal conditions were found at a pH of 2 for acid red 88 and pH 10 for crystal violet, with a contact time of 80 min and an adsorbent dosage of 0.05 g in a 100 mL solution. Under these conditions, the sample synthesized using succinic acid achieved sorptive capacities of 452.49 mg/g for acid red 88 and 446.43 mg/g for crystal violet, while the sample synthesized using malic acid reached 408.16 mg/g and 374.53 mg/g, respectively. Both adsorption processes followed the pseudo-second-order kinetic model and aligned with the Langmuir isotherm. Thermodynamic analysis confirmed the process as exothermic and spontaneous. Practical trials demonstrated removal efficiencies above 95% for both dyes in real wastewater samples, underscoring the method’s practical potential in water purification applications.